Marketing analysis of the higher education service sector in Malaysia: consumer perspective - Hussin, Siti Rahayu; Tan, Ho Soon; Md. Sidin, Samsinar (Universiti Putra Malaysia Press, 2000)
Like many other service organizations, higher education institutions may want to review their marketing strategies in order to complete in the increasingly competitive market. It is crucial that higher learning institutions understand the perceptions and expectations of students and translate them into marketing activities that would attract and retain students. The objective of the research is to explore student view on important criteria in selecting higher education institutions. Personal interviews with 210 student from both public and private higher learning institutions in Malaysia were carried out. Variables used include: academic programme, academic staff, facilities, pricing, and promotion. Data were analysed using Factor Analysis and Comparison of Means. Based on the study, students consider personal factors (job opportunities, availability of course, time required for completion, entry requirements, availability of part-time studies, marketability of degree); academic quality and facilities (quality of teaching, library collection, institution's reputation, facilities, programme structure); campus (campus size and layout, campus attractiveness, number of students); socialization (extra curricular activities, opportunity to meet friends); and financial aid & procedures (scholarship/financial aid, procedures and policies) as important criteria in selecting a higher learning institution. Based on Comparison of Means, rankings of variables influencing college choice decision by importance are as follows: quality of teaching, institution's reputation, marketability of degree, job opportunities, tuition fees, programme structure, time required for completion, facilities, availability of courses, and entry requirements.